The Practice of Allergen Immunotherapy among Allergists in the Philippines - Kasala, Maria Carmela; Distor, Cherry Ann; Elorde, Aileen; Otadoy-Agustin, Jenifer; Quiambao, Maria Bettina; Castor, Mary Anne; Recto, Marysia Stella (Philippine Journal of Allergy, Asthma and Immunology, 2024)
Background: Allergic conditions continue to increase globally. Allergen Immunotherapy (AIT) is a therapeutic option for allergic rhinitis and asthma. This treatment can alter the natural course of the disease and provide potential cure. In the early 1970s, allergists in the Philippines began using AIT, specifically Subcutaneous Immunotherapy (SCIT). Forty years later, Sublingual Immunotherapy (SLIT) was introduced. To date, there are still no published studies on the clinical practice of AIT among allergists in the Philippines. Objective: The objective of the study was to assess the practice of allergen immunotherapy among allergists in the Philippines. Methodology: This cross-sectional study surveyed Filipino allergists in 2019. The survey consisted of a 15-point questionnaire administered to active members of the Philippine Society of Allergy, Asthma and Immunology. Results: Sixty allergists responded to the survey. Ninety percent of these allergists prescribed immunotherapy to their patients. Extracts used are mostly house dust mite, cockroach, grass, and animal dander. The subcutaneous route was the most frequently used (68.5%), followed by both subcutaneous and sublingual (27.8%), then sublingual alone (3.7%). Although 41 out of 60 (68.3%) allergists surveyed have not tried SLIT for their patients, these same allergists were open to the idea of using SLIT in the future. Conclusion: Despite difficulties in the procurement of AIT materials, Filipino allergists have been prescribing AIT for patients with allergic rhinitis and asthma as recommended by global guidelines. SCIT is more widely used than SLIT.